Impact of the use of e-cigarettes on various problems related to oral health: scoping review - Curo-Valdivia, Yuri Freddy; Peña-Chuctaya, Marice Levi; Lecca-Dominguez, Stefany Erika; Llique-Sánchez, Alejandro Manuel; Riofrío-Ramírez, Maricarmen Elizabeth; Delgado-Asmat, Edith Esther (Revista Facultad de Odontología Universidad de Antioquia, 2025)
Introduction: The consumption of electronic cigarettes has increased globally, especially among young people. Recent studies indicate adverse impacts on oral tissues and the oral microbiota, as well as an increased risk of various oral diseases. The aim was to synthesize the available evidence regarding the effects of electronic cigarettes on oral health. Methods: A scoping review was conducted following the PRISMA-ScR guidelines, analyzing studies published between 2018 and 2024 in PubMed, Scopus, Web of Science, SciELO, and LILACS. A total of 47 articles were selected from an initial pool of 720, applying inclusion criteria for articles in English and Spanish that evaluated the impact of electronic cigarettes on various aspects of oral health. Results: Negative effects on periodontal health, changes in the oral microbiota, dental caries, and saliva production; cellular and tissue alterations; dental aesthetics, peri-implant health, oral health-related quality of life, oral hygiene, and the proliferation of Candida albicans are highlighted. In general, the use of these devices promotes gingival inflammation, alters the composition of the oral microbiota, and affects saliva production, factors that increase the risk of caries and periodontitis. Additionally, some compounds in the vapor from electronic cigarettes, such as flavorings, may induce cytotoxicity and changes in the structure of dental materials, affecting their stability and aesthetics. Conclusions: Although electronic cigarettes present fewer risks than conventional tobacco, their impact on oral health should not be underestimated.